An Open Future: Why Alternate Histories Sometimes Qualify as Future Narratives (KULT_online, 2014)
The two reviewed volumes frame a five volume book series on "Future Narratives", a group of texts that has been researched in the project "Narrating Futures". Future narratives qualify as such if they possess at least one "node", a textual element which "allows for more than one continuation" (Bode/Dietrich p. 1). While Future Narratives by Bode/Dietrich explores the definition of this group of texts, Singles writes on Alternate History as a genre that in some cases has overlaps with future narratives.